2015
DOI: 10.1152/jn.00841.2014
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of parvalbumin- or somatostatin-expressing interneurons triggers epileptic seizurelike activity in mouse medial entorhinal cortex

Abstract: GABAergic interneurons are thought to play a critical role in eliciting interictal spikes (IICs) and triggering ictal discharges in temporal lobe epilepsy, yet the contribution of different interneuronal subtypes to seizure initiation is still largely unknown. Here we took advantage of optogenetic techniques combined with patch-clamp and field recordings to selectively stimulate parvalbumin (PV)- or somatostatin (SOM)-positive interneurons expressing channelrhodopsin-2 (CHR-2) in layers II-III of adult mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
132
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 72 publications
13
132
3
Order By: Relevance
“…14 Here, we have confirmed the contribution of PV interneurons to LVF discharges using a novel strain with a PV-Cre background in which we provided the enhanced ChR2 opsin, ChETA, using a stereotaxic virus injection procedure. In addition, as recently reported by Yekhlef et al, 33 we found that the optogenetic activation of SOM interneurons in EC is also sufficient to trigger LVF onset events.Because previous studies have shown that GABA application to the dendrites induces depolarizing responses, whereas its application to the soma results in hyperpolarization, [34][35][36][37] we anticipated differences in the ability of somatic-targeting PV and dendritic-targeting SOM interneurons to trigger ictal discharges in the EC network. In addition, PV interneurons innervate twice as many principal cells as other interneurons and receive more local excitatory input 38 ; therefore, we expected these cells to play more preponderant roles compared to other interneuron types in triggering of ictal discharges.…”
supporting
confidence: 90%
“…14 Here, we have confirmed the contribution of PV interneurons to LVF discharges using a novel strain with a PV-Cre background in which we provided the enhanced ChR2 opsin, ChETA, using a stereotaxic virus injection procedure. In addition, as recently reported by Yekhlef et al, 33 we found that the optogenetic activation of SOM interneurons in EC is also sufficient to trigger LVF onset events.Because previous studies have shown that GABA application to the dendrites induces depolarizing responses, whereas its application to the soma results in hyperpolarization, [34][35][36][37] we anticipated differences in the ability of somatic-targeting PV and dendritic-targeting SOM interneurons to trigger ictal discharges in the EC network. In addition, PV interneurons innervate twice as many principal cells as other interneurons and receive more local excitatory input 38 ; therefore, we expected these cells to play more preponderant roles compared to other interneuron types in triggering of ictal discharges.…”
supporting
confidence: 90%
“…Recent optogenetic studies also lead to conflicting views on the role of inhibition in epilepsy. In seizure models in vivo (KrookMagnuson et al, 2013;Paz et al, 2013), optogenetic activation of GABAergic interneurons was found to suppress ongoing epileptiform activities, whereas in other models in vitro optogenetic activation of Pv interneurons and, although less efficiently, somatostatin interneurons enhanced spontaneous ictal events (Shiri et al, 2014;Yekhlef et al, 2014). Our study reconciles these conflicting views by revealing that, in the same model of epileptiform activity, Pv interneurons play a dual opposing role, either favoring the generation or opposing the propagation of ictal events.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, GABAergic interneurons, and in particular parvalbumin (Pv)-expressing interneurons, can generate a feedforward inhibition that opposes seizure spread in both experimental models (Trevelyan et al, 2006; and patients (Schevon et al, 2012). Moreover, whereas studies in brain slices suggest that optogenetic activation of GABAergic interneurons can enhance epileptiform activity (Shiri et al, 2014;Yekhlef et al, 2014), optogenetic in vivo studies reveal that Pv interneuron activation interrupts spontaneous ongoing seizures (Krook-Magnuson et al, 2013;Paz et al, 2013). Optogenetics was thus proposed as a promising approach for those epilepsies, such as temporal lobe epilepsy, that have typical activity arising from restricted epileptogenic sites.…”
Section: Introductionmentioning
confidence: 99%
“…Within the dentate gyrus, the ␦ subunit of the GABA A R is the major mediator of tonic inhibition in granule cells and some interneurons (Glykys et al, 2008;Lee and Maguire, 2013;Yu et al, 2013), including interneurons in the dentate molecular layer and parvalbumin-expressing interneurons along the base of the granule cell layer (Peng et al, 2004;Glykys et al, 2007;Milenkovic et al, 2013). In sharp contrast, the vast majority of somatostatin (SOM) neurons in the dentate hilus lack labeling for either the ␦ subunit or other GABA A R subunits that are likely to mediate tonic inhibition (Esclapez et al, 1996;Milenkovic et al, 2013).…”
Section: Introductionmentioning
confidence: 99%